How can Green Public Procurement contribute to Social Sustainability? - Raquel Carvalho (Foro, Revista de Derecho)
Much has already been written about secondary policies, and then promoted to horizontal and now almost on a par with the primary objective of public procurement-competition. It should be noted that European jurisprudence, followed by the Public Procurement Directives, has always limited the use of public procurement as a vehicle for the promotion of environmental, social and sustainable development policies, which has recently become increasingly emphasised with the transition from linear to circular economy. For reasons linked to the cross-cutting nature of environmental policies and the national economic connection of social policies, the former are more suited for harmonising member states’ legal systems. As a result, the promotion of the social impact of public procurement is often limited to matters in which the European Union legislates —the labour feld— or to the more primary dimensions of constitutionality associated with the principle of equality and Human Rights. Our re?ection therefore aims to go beyond what European case law and directives enshrine and recognise, asking whether environmental policies might contribute to social sustainability as well. We will try to prove this by presenting practical examples. The cases presented, as a method, are meant to be a “proof of concept”.